Paris - New-York. - Centre Georges Pompidou (Paris : Centre Georges Pompidou, 1977)
Alechinsky, Pierre ; Andre, Carl ; Archipenko, Aleksandr ; Arman ; Arp, Hans (Jean) ; Balthus ; Berman, Eugene ; Bolotowsky, Ilya ; Brancusi, Constantin ; Braque, Georges ; Brauner, Victor ; Brecht, George ; Breer, Robert ; Breton, André ; Bruce, Patrick Henry ; Brusse, Mark ; Bryen, Camille ; Bury, Pol ; Cahn, Marcelle ; Calder, Alexander ; Carles, Arthur B. ; César ; Cézanne, Paul ; Chagall, Marc ; Chamberlain, John ; De Chirico, Giorgio ; Christo ; Conner, Bruce ; Cornell, Joseph ; Covert, John ; Crotti, Jean ; Csáky, József ; Dali, Salvador ; Dasburg, Andrew ; Davis, Stuart ; Delaunay, Robert ; Delaunay, Sonia ; Delvaux, Paul ; Demuth, Charles ; Derain, André ; Diller, Burgoyne ; Dine, Jim ; van Doesburg, Theo ; Domela, César ; Dominguez, Oscar ; Donas, Marthe ; Dove, Arthur ; Dreier, Katherine ; Dubuffet, Jean ; Duchamp, Marcel ; Duchamp-Villon, Raymond ; Einstein, William ; Ernst, Max ; Errò ; Fahlström, Öyvind ; Filliou, Robert ; Riverhead (New York) ; Francis, Sam ; Fresnaye, Roger de la ; Freytag-Loringhoven, Elsa Von ; Frost, Arthur Burdett ; Gabo, Naum ; Gauguin, Paul ; Giacometti, Alberto ; Glarner, Fritz ; Gleizes, Albert ; van Gogh, Vincent ; Golub, Leon ; Gorin, Jean ; Gorky, Arshile ; Gris, Juan ; Hains, Raymond ; Halicka, Alice ; Halpert, Samuel ; Hartley, Marsden ; Hartung, Hans ; Hayter, Stanley William ; Hélion, Jean ; Henri, Florence ; Herbin, Auguste ; Hirshfield, Morris ; Jean, Marcel ; Johns, Jasper ; Kandinsky, Wassily ; Kaprow, Allan ; Kelly, Ellsworth ; Kienholz, Edward ; Klein, Yves ; Kline, Franz ; de Kooning, Willem ; Kupka, Frantisek ; Lachaise, Gaston ; Lam, Wifredo ; Laurencin, Marie ; Laurens, Henri ; Leger, Fernand ; Lichtenstein, Roy ; Lipchitz, Jacques ; Louis, Morris ; MacDonald Wright, Stanton ; Magritte, René ; etc.
boek